Um lugar para o tempo dos letrados: leituras, leitores e a Biblioteca Provincial do Ceará na segunda metade do século XIX - Pinheiro Filho, José Humberto Carneiro (2014)
In 1915, one of the most widely read novels in the Provincial Library of Ceará from 1878 to 1887, The Adulterous Woman, by the Spanish Enrique Perez Escrich, was defined, in a kind of index, as "an unworthy work for household". Definitions like that one were not uncommon during the XIX century, when there was talk of novelistic stories. At that time, reading a novel was done among several impasses and interests, that is, consuming fiction books was a practice discussed by many crossed speeches. That is why speaking about historical uses of reading is to contribute to an analyses of book culture and of its place and meaning in a particular historical situation. Our work discusses the reading practices in the Provincial Library of Ceará, in the perspective of a critical mapping of books circuit in Fortaleza in the last decades of the XIX century.